In situ detection of fatty acid C=C positional isomers by coupling on‐tissue mCPBA epoxidation with infrared matrix‐assisted laser desorption electrospray ionization mass spectrometry. (30th May 2021) - Tu, Anqi; Garrard, Kenneth P.; Said, Neveen; Muddiman, David C.
Abstract : Rationale: Unsaturated fatty acids (UFAs) play vital roles in regulating cellular functions. In‐depth structural characterization of UFAs such as localizing carbon–carbon double bonds is fundamentally important but poses considerable challenges in mass spectrometry (MS) given that the most widely accessible ion activation method, low‐energy collision‐induced dissociation (CID), primarily generates uninformative fragments (e.g., neutral loss of CO2 ) that are not suggestive of the double‐bond positions. Methods: m ‐Chloroperoxybenzoic acid (mCPBA) was uniformly deposited onto the sample slides using a TM Sprayer, converting the carbon–carbon double bonds into epoxides under ambient conditions. The epoxidation product was ionized in situ by infrared matrix‐assisted laser desorption electrospray ionization mass spectrometry (IR‐MALDESI‐MS), and subsequently cleaved via CID, generating a diagnostic ion pair associated with the double‐bond position. The reaction efficiency, sensitivity and relative quantification capability of the method were validated with five UFA standards dried on glass slides, and then this strategy was demonstrated on thin tissue sections of rat liver and human bladder. Results: The mCPBA reaction yielded conversion rates in the range of 44–60% in 10 min with high specificity and sensitivity. Further tandem mass spectrometry (MS/MS) of the mono‐epoxidized products generated informative fragment ions specific to the double‐bond positions, and relative quantification of positional isomers in binary mixtures was performed across a wide mole fraction from 0 to 1. An innovative spiral scan pattern was utilized during data acquisition, elucidating the major isomeric compositions of multiple UFAs from a tissue section in a single run. Conclusions: The on‐tissue mCPBA epoxidation was implemented into an ambient MS imaging workflow to offer a rapid and simple way for in situ identification and relative quantification of double‐bond positional isomers without the requirement for instrument modification. The method can be readily implemented on many other MS platforms to reveal the role of double‐bond positional isomers in lipid biology and to discover potential biomarkers.